ANALISIS NILAI PERUSAHAAN PADA SEKTOR PERTAMBANGAN BATUBARA DI BURSA EFEK INDONESIA - Wijayanti, Iin; Nur, Dhani Ichsanuddin; B, Gideon Setyo (Universitas Muhammadiyah Ponorogo, 2016)
This study aimed to examine the effect of inflation, liquidity and leverage on Â corporate performance, the effect of inflation, liquidity, leverage and performance of the company against the value of the company as well as the effects of inflation, liquidity and leverage the value of the company through the company's performance. This research is quantitative. The sampling method used is purposive sampling with a sample of 85 financial statement data. Methods of data collection using secondary data obtained from the web the Indonesia Stock Exchange (www.idx.com). Analysis of data in this study using the path analys. Findings from this study indicate that inflation can not contribute to the improvement of the company's performance, liquidity, leverage and inflation may contribute to the increased value of the company, liquidity may contribute to the increased value companies, leverage can contribute increased value of the company, the company's performance can contribute to increase the company's value, inflation contributed to the rise of the value of the company through the company's performance. Liquidity contribute to the enhancement of the corporate value through corporate performance. Leverage contribute to the improvement of the company's value through